Jual Beli Produk Tupperware Bergaransi Seumur Hidup Menurut Hukum Islam - Ayu Darnis; Bahrul Ma'ani; Pidayan Sasnifa (Postgraduate Studies UIN Sulthan Thaha Saifuddin Jambi, 2016)
This study aims to determine the perspective of Islamic law regarding the implementation of the system of buying and selling tupperware products that have a lifetime guarantee at PT. Nazila Jambi Nugraha Simpang Kawat, Jambi City. Another purpose of the research is to find out the positive impact of this system for sellers and buyers of tupperware products. Using a qualitative approach with data collection methods through interviews, documentation, and observation, the results of the study found: first, the distributor company has given books or catalogs to retail sellers or resellers as well as members or members to sell these products at prices listed for each product . Distributors give a discount of 30% for the resseller or member. Second, the view of Islamic law on the sale and purchase of tupperware products that are guaranteed, according to Islamic law there is still an element of openness regarding providing a lifetime guarantee. In the contract there must be openness between the two parties to avoid the existence of elements of fraud. Third, the positive impact on sellers and buyers is equally beneficial. For sellers to benefit and add friendship, buyers get the benefits of tupperware products.